Historical-philological Annotations on Self-Generation in Kant - Azevedo Marques, Ubirajara Rancan de [UNESP] (Franco Angeli, 2017)
The word Selbstgebeirung occurs only once in the Critique of Pure Reason. Likewise, it does not seem to appear in any other text of Kant, and no other reference is to be found that precedes this occurrence. Hence, I assume that Selbstgebarung is a neologism of the philosopher's making, and that it may have resulted from the condensation of two terms whose mutual vicinity had long been established in the mystical-theosophical field. Throughout the present study, I shall examine the origin of the expression, the philological difficulties inherent to its understanding, and the elements pertaining to a self-generation of the understanding.
Keywords: Critique of Pure Reason; Selbstgebarung; epigenesis; equivocal generation; spontaneous generation; self-generation of the understanding